Effect of low-temperature annealing on Bi-poor Cs2AgBiBr6 single crystals. (December 2022) - Cao, Da; Yang, Ge
Abstract: All-inorganic double perovskite Cs2 AgBiBr6 has attracted increasing research interest due to its great potential for optoelectronic applications. To date, most studies focus on the room-temperature characteristics of as-grown Cs2 AgBiBr6 single crystals. In this work, we investigated the effect of low-temperature annealing on the physical properties of Cs2 AgBiBr6 single crystals. The studied Cs2 AgBiBr6 single crystal was grown using a Bi-poor precursor and has a bandgap of 2.12 eV, showing superior elastic properties with Young's modulus at 32 GPa and hardness at 1 GPa. When the annealing temperature increased from 25 °C to 80 °C, the resistivity of the as-fabricated Bi-poor Cs2 AgBiBr6 crystal decreased from 8.07 × 10 9 Ω cm to 5.86 × 10 7 Ω cm. Interestingly, the room-temperature resistivity of the annealed Cs2 AgBiBr6 increased nearly 3 times when compared to the original value before the annealing. After the annealing, the Cs2 AgBiBr6 crystal still holds a strong response to radiation sources. The temporal response of the Cs2 AgBiBr6 crystal under the 568-nm LED illumination also indicated that the rising time and the decaying time are much shorter than the initial values before the annealing. These results demonstrate a robust thermal and air stability of Bi-poor Cs2 AgBiBr6 single crystal. An effective annealing strategy could play an important role in tuning the fast decay- and rise-time characteristics of Cs2 AgBiBr6 single crystals. Graphical Abstract: ga1 Highlights: Fabricated Bi-poor Cs2 AgBiBr6 single crystals and studied the effect of low-temperature annealing on it. The resistivity increased nearly 3 times after the annealing temperature up to 80 °C. The fabricated device showed a strong response to gamma sources and LED illumination of 568 nm before and after annealing. The response time to LED illumination enhanced a lot after low-temperature annealing.